Ungkapan Mitos Kehamilan Perspektif Tokoh Agama dan Strukturasinya pada Generasi Milenial di Provinsi Kepulauan Bangka Belitung - Harista, Eva; Bohhori, Bohhori; Firdaus, Wahyu (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
The aim of this study is to describe the variety of expression of the myth of pregnancy and its implementation in the millennial generation in the Bangka Belitung Islands Province. This type of research is field research, using descriptive qualitative and quantitative research methods. The research approach is a sociological approach using the mythical structuralist theory of Claude Levi-Strauss. The results of this study show that there are twenty-one different myths during pregnancy that develop in the community in the province of Kepualauan Bangka Belitung. This pregnancy myth contains about anxieties or prohibitions that have a certain impact if followed or not followed for the society that believes in it. Of the 120 millennial respondents who answered about the implementation of pregnancy myths, it was found that 30.8 percent had implemented a myth during pregnancies, 28.3 percent sometimes implemented the myth while pregnant, and 40.8 percent never implemented myth when pregnant. Thus, it can be concluded that the millennial generation is still quite a lot that implements both the myth of prohibition and abortion during pregnancy. This means that many millennials still believe and still believe in the leaders or ancestors of the parents / elders or cultures / traditions spread in the community environment where they live. The results of this research are in line with Claude Levi-Strauss’s theory of structural patterns of mythology, namely about human myths and intuitions, mythos and language, the structure of the myth, as well as myth and social values.